Técnica de intervenção judicial nos contratos: pressupostos - Martins, César Barbosa (2008)
The dissertation focuses on the analysis of conditions which allow judicial review and intervention of contracts when supervening facts that cause substantial variation to the terms and conditions occur. Thus, the objective was to make an approach towards the legal requisites for contractual review and dissolution, based on principles of Brazilian Law, once the contract is distorted due to a subsequent fact. Such work required a historical study, in order to obtain the elementary premises that authorize judicial review and intervention of contracts. In this manner, among other topics, the study of the classic and origin-debated rebus sic stantibus clause was the main theoretical reference for research of the topic. Furthermore, judicial contractual review and dissolution requisites in both Brazilian and foreign legal systems were likewise studied. Without doubt, the approach towards international legal investigation was the primary source of progressive research of the possibilities of relativization of the pacta sunt servanda dogma